Memotret Perlakuan Akuntansi Zakat Sebagai Wujud Akuntabilitas Badan Amil Zakat Nasional (BAZNAS) Gorontalo - Marina Paramitha Sari Piola; Melinda Ibrahim; Rahmatia Rahmatia (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study aims to capture the accounting treatment of zakat based on PSAK 109 at Province, City, and Regency Indonesia’s National Zakat Agency (BAZNAS) in Gorontalo. A qualitative approach with comparative study is designed to explore the holistic reality. The results showed that the National Zakat Agency of Gorontalo Province and Gorontalo City have already referred to the PSAK 109 in their recognition, measurement, and disclosure. Meanwhile, their non-compliance has been found in their presentation and reporting. Meanwhile, the Baznas of Gorontalo Regency and Bone-Bolango Regency have standardized their accountability by still implementing the internal standards regulated by Baznas The lack of skillful human resources has affected the performance of Baznas in the implementation of the PSAK 109. However, BAZNAS has admitted its unstandardized reporting, but claimed it to be still under the regulation format based on the regulation of Indonesia’s National Zakat Agency Number 14 of 2014.